Bubbles, bank credit and macroprudential policies - Alexis Derviz (European Central Bank (ECB), 2013)
We explore the ability of a macroprudential policy instrument to dampen the consequences of equity mispricing (a bubble) and the correction thereof (the bubble bursting), as well as the consequences for real activity in a production economy. In our model, producers are financed by both bank debt and equity, and face a mix of systematic and idiosyncratic uncertainty. Positive/negative bubbles arise when prior public beliefs about the aggregate productivity of producers (business sentiment) become biased upwards/downwards. Economic activity in equilibrium is influenced by the bubble size. The presence of macroprudential policy is represented by a convex dependence of bank capital requirements on the quantity of uncollateralized credit. We find that this kind of policy is more successful in suppressing equity price swings than moderating output fluctuations. Economic activity declines with the introduction of a macroprudential instrument in this model, so that the ultimate welfare contribution of the latter would depend on the aggregate default costs.
Keywords: G01; G21; G12; E22; D82; 330; asset price; bank; bubble; credit; Macroprudential policy